Kewarganegaraan Multikultural dalam Negara Hukum : Antara Hak Asasi dan Kepentingan Nasional - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Saela Noviana; Noviana Nurfitriani; Teshana Mutiara Hati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Human rights must be weighed against the state's interests, especially in a multicultural society. The concept of multicultural citizenship often conflicts with state policy priorities they defense of personal liberties. The state must recognize and protect cultural, religious, and ethnic diversity. Inversely proportional, social stability and national integration are top priorities. This study examines different theories of citizenship, the fundamentals of the rule of law, as well as the problem of managing diversity in a democratic legal system. A descriptive qualitative approach is used in this study to examine policies and regulations related to multicultural citizenship in Indonesia and how they impact human rights and national interests. The results show that despite regulations that assist inclusion, the application of anti-discrimination and the use of policies is still difficult. Therefore, to accept diversity without sacrificing human rights or national interests, more equitable, inclusive, and flexible policies are needed.